Beers, beers, good for the heart?. Issue 5 (May 2016) - Lyon, Corey
Abstract : N/A: Smyth A, Teo KK, Rangarajan S, et al. Alcohol consumption and cardiovascular disease, cancer, injury, admission to hospital, and mortality: a prospective cohort study. Lancet . 2015; 386(10007):1945–1954.